Cloning, organization, and expression of the bioluminescence genes of Xenorhabdus luminescens. - Frackman, S (1990)
The lux genes of Xenorhabdus luminescens, a symbiont of the nematode Heterorhabditis bacteriophora, were cloned and expressed in Escherichia coli. The expression of these genes in E. coli was qualitatively similar to their expression in X. luminescens. The organization of the genes is similar to that found in the marine luminous bacteria. Hybridization studies with the DNA that codes for the two subunits of luciferase revealed considerable homology among all of the strains of X. luminescens and with the DNA of other species of luminous bacteria, but none with the nonluminous Xenorhabdus species. Gross DNA alterations such as insertions, deletions, or inversions do not appear to be involved in the generation of dim variants known as secondary forms.